Detrital zircon U-Pb geochronology, Hf isotopes and geochemistry constraints on crustal growth and Mesozoic tectonics of southeastern China - Meng, L.; Li, Zheng-Xiang; Chen, H.; Li, X.; Zhu, C. (Elsevier Ltd, 2014)
In situ U–Pb geochronological, Hf isotopic and REE geochemical analyses of detrital zircons from Mesozoic sandstones in central Jiangxi and east Hunan of the South China Block (SCB) are used to provide not only information about crustal evolution process, but more importantly new constraints on sedimentary provenances as well as Mesozoic basin evolutions in central SCB. A total of 417 concordant zircon analyses define five U–Pb age populations at ca. 2.6–2.3 Ga, ca. 2.0–1.7 Ga, ca. 1.0–0.7 Ga, ca. 500–400 Ma and ca. 300–200 Ma. Integrated analyses of zircon U–Pb ages and Hf isotopes of detrital zircons reveal five episodes of juvenile continental crust growth: ca. 2.5 Ga, ca. 1.7 Ga, ca. 850 Ma, ca. 440 Ma and ca. 230 Ma, with all but the ca. 2.5 Ga episode likely represent that of the SCB.None of the three samples from T3–J1 strata showed strong ca. 1850 Ma and ca. 230 Ma peaks suggesting that the T3–J1 sediments probably sourced from the Yangtze Block. In contrast, stronger peaks of ca. 1850 Ma and ca. 250–230 Ma in post-J1 strata relative to that of T3–J1 strata suggest a dominantly local Cathaysian provenance. In addition, the distinct low εHf(T) values for zircons of ca. 430 Ma from T3–J1 strata in comparison with higher εHf(T) values for that from post-J1 strata also support aforementioned viewpoint. Such sharp changes between the pre-J1 and post-J1 strata coincide with the remarkable change in regional palaeogeography from a broad shallow marine basin in the Late Triassic–Early Jurassic time to a basin-and-range-style province in the Middle Jurassic. The characteristics and time evolution of detrital zircons from the studied area are consistent with the flat-slab subduction model which involves the development of a broad sag basin during the T3–J1 time, and a rapid regional uplift in the Cathaysia Block caused by the reinitiating of normal subduction along the coastal region at ca. 190 Ma.